The impact of socio-economic determinants on rural poverty in Pakistan - Tasleem, Zerish (2022)
The objective of this study is to explore the socio-economic determinants of poverty in the rural area of Southern Punjab, Pakistan. These rural areas of Southern Punjab were selected because the poverty rates are higher in these areas if compared to urban areas. The rural poverty happens due to many factors such as high dependency rate, lack of education, lack of health facilities and low per capita income. The moderating effect of culture was also taken into considerations in this study. Cultural Belief Systems Theory together with the Cumulative and Cyclical Interdependency Theory was adopted in this study because both are among the major theories and often used in the poverty eradication studies, and in various other fields of research too. Based on the essence of both theories, this study hypothesized that socio-economic determinants have positive impact on rural poverty and culture moderates these relationships. Research data were collected through cross-sectional method and the sample consisted of 444 households. The data were analysed using Statistical Package for Social Sciences (SPSS) and Smart Partial Least Square (Smart PLS) software. SPSS was used for descriptive data analysis whereas Smart PLS was used for the inferential analysis. The findings of this study unveil that the socio-economic determinants namely education, health and income were significantly related to rural poverty, whereas the population has negative effects on rural poverty. Culture has a moderation effect on the relationship between educations, health and income with rural poverty but it exerts no moderation effect on the relationship between population and rural poverty. As the result of this study exhibits that socio-economic determinant are the key towards alleviation of rural poverty, it is recommended that the policy makers should developed appropriate strategies which focused on poverty eradication and the development of the nation. It is suggested that promoting education among the rural people, providing more educational opportunity so that the dependency rate may be reduced, and provision of basic necessities for everyday life in the rural areas may help reduce the poverty rate. Finally, the findings of this study hopefully will pave the way for further improvements in rural development and poverty alleviation in Pakistan.